Ancient rice cultivar extensively replaces phospholipids with non‐phosphorus glycolipid under phosphorus deficiency. Issue 3 (27th April 2018) - Tawaraya, Keitaro; Honda, Soichiro; Cheng, Weiguo; Chuba, Masaru; Okazaki, Yozo; Saito, Kazuki; Oikawa, Akira; Maruyama, Hayato; Wasaki, Jun; Wagatsuma, Tadao
Abstract : Recycling of phosphorus (P) from P‐containing metabolites is an adaptive strategy of plants to overcome soil P deficiency. This study was aimed at demonstrating differences in lipid remodelling between low‐P‐tolerant and ‐sensitive rice cultivars using lipidome profiling. The rice cultivars Akamai (low‐P‐tolerant) and Koshihikari (low‐P‐sensitive) were grown in a culture solution with [2 mg l −1 (+P)] or without (−P) phosphate for 21 and 28 days after transplantation. Upper and lower leaves were collected. Lipids were extracted from the leaves and their composition was analysed by liquid chromatography/mass spectrometry (LC–MS). Phospholipids, namely phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylglycerol (PG) and phosphatidylinositol (PI), lysophosphatidylcholine (lysoPC), diacylglycerol (DAG), triacylglycerol (TAG) and glycolipids, namely sulfoquinovosyl diacylglycerol (SQDG), digalactosyldiacylglycerol (DGDG), monogalactosyldiacylglycerol (MGDG) and 1, 2‐diacyl‐3‐O‐alpha‐glucuronosyl glycerol (GlcADG), were detected. GlcADG level was higher in both cultivars grown in −P than in +P and the increase was larger in Akamai than in Koshihikari. DGDG, MGDG and SQDG levels were higher in Akamai grown in −P than in +P and the increase was larger in the upper leaves than in the lower leaves. PC, PE, PG and PI levels were lower in both cultivars grown in −P than in +P and the decrease was larger in the lower leaves than in the upper leaves and in Akamai than in Koshihikari. Akamai catabolised more phospholipids in older leaves and synthesised glycolipids in younger leaves. These results suggested that extensive phospholipid replacement with non‐phosphorus glycolipids is a mechanism underlying low‐P‐tolerance in rice cultivars.